The Benefits of Physical Activity in Children and Adolescents with Epilepsy: A Systematic Review - Svierkovski, Loyane de Fátima; Stein, Angelica Miki; Cavazzotto, Timothy; Paludo, Ana Carolina (Journal of Pediatric Epilepsy, 2021)
The aim of this study was to review the literature about the effect of physical activity intervention in children and adolescents with epilepsy. Articles were searched in the central electronic databases of MEDLINE, Embase, PsycAriticles, and CINAHL for the following keywords: “epilepsy,” “seizure,” “physical activity,” “physical exercise,” “exercise therapy,” “sport,” using the Boolean operator “AND” and “OR.” The quality of the selected articles was evaluated by the Physiotherapy Evidence Database scale. Out of the 22 articles selected, 18 did not involve intervention or did not have pre- and postresults and therefore were excluded from the study. The remaining four were studies from Canada and Korea which comprised two long-period interventions and were included in the analysis. Both programs demonstrated a positive effect of physical activity on variables related to psychological well-being and cognitive function. All the four articles demonstrated a lower score of quality. In conclusion, reviewed studies suggest that physical exercise program induces some benefits in children and adolescents with epilepsy. However, the noncontrolled trials and the varied analyses (quantitative vs. qualitative) make it difficult to establish a consensus about benefits of physical activity in epilepsy.
Keywords: adolescents; children; epilepsy; exercise; physical activity